Respon Saham Sektor Industri Barang Konsumsi Terhadap Guncangan Makroekonomi Pada Periode Covid 19 - Simanjuntak, Lasmaria Fitri; Yudo Nugroho, Ris Yuwono (Magister Manajemen STIE Bank BPD Jateng, 2024)
This research aims to analyze the response of commodity prices of consumer goods to changes in shocks given by inflation, interest rates, and exchange rates to find out the dynamic patterns between the independent and dependent variables. The data used in this study is in the form of monthly time series data during the COVID-19 pandemic, namely from January 2020 to December 2022. The research uses a quantitative approach with the Vector Error Correction Model (VECM) analysis method. The analysis techniques used are the unit root test, optimal lag test, stability test, cointegration test, VECM test, impulse response function test, and variance decomposition test. The research results show that commodity prices for consumer goods respond negatively and significantly to changes in inflation and interest rates. Meanwhile, due to changes in exchange rates, commodity prices for consumer goods respond positively and significantly. The dynamic patterns can be seen in the impulse response and variance decomposition tests. In the impulse test, the price response of consumer goods and commodities responds negatively to changes in inflation and interest rates. On the other hand, the exchange rate was positively responded to by commodity prices for consumer goods. In the variance decomposition test, the sector's share price is the most significant variable that influences the stock price of consumer goods and commodities, followed by the exchange rate variable